Studi Randomized Clinical Trial (RCT) Terapi Gizi pada Anak dengan ADHD: Literature Review: Randomized Clinical Trial (RCT) Study of Nutrition Therapy in Children With ADHD: Literature Review - Miladitiya, Aulia (UNIVERSITAS NGUDI WALUYO, 2024)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurological behavioral problem seen in children, associated with learning disorders, impulsive behavior, hyperactivity, and inability to concentrate. Global Burden of Disease data in 2019 shows that the highest prevalence of children with ADHD aged 10-14 years is 2.9%. Adjusting diet and nutrition is a consideration to improve ADHD symptoms. This literature review aims to determine macro and micronutrients that have benefits in nutritional therapy for children with ADHD based on the results of RCT studies. The review was carried out by searching the literature on the PubMed database with the keywords